LEADERSHIP CHALLENGES FACING THE DEMANDS OF INDUSTRY 4.0 - Caroline Rigolin, Darlene; de Souza Santos, Elinete; Carlos da Costa, Elvio (Revista Interface Tecnológica, 2022)
The present article had as main objective to evaluate the transformations and evolution of technology, aiming at improving productivity, processes and efficiency related to the speed and flexibility of production, exerting transformations on contemporary organizations. It also aimed to show the difficulties and skills presented in the day-to-day of these leaders and the need to reinvent themselves to stay in the job market. The methodology used was a bibliographic survey in a database of greater relevance of scientific works already carried out and the application of a case study in a retail furniture company in the city of Araraquara, and as a data collection instrument we used a interview conducted with 11 leaders of the company in question, in order to identify positive and negative points in relation to this new scenario. We obtained as a result that the biggest difficulties presented are the interpersonal and motivational relationship between leaders and follwers and the training and development of leaders.
Keywords: Fourth Revolution; Technologies; Leadership; Motivation; Communication